Humanizing the Classroom Method Toward the Students’ Ability in Writing Descriptive Text - Nurul Fadilah; Hastuti Retno Kuspiyah (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2018)
The problem of this research was to find out whether or not there was any significant difference between the students who are taught using humanizing the classroom method and those who are taught using conventional method. And the methodology of the research used experimental method, by quasi-design. Meanwhile, the population was the tenth-grade students of MA NU Sumber Agung OKU Timur, Sumatera Selatan. It consists of 60 students, used purposive sampling technique. And there were 42 students as a sample of this research. In collecting the data, the researchers used the written test as the instrument to obtain the students' ability in writing descriptive text. And for analyzing the data using independent t-test. The data distribution was considered normal. It was proved by statistics calculation of normality test which shows that < or 9,72 < 11,07 in experimental class and < or 2,99 < 11,07 in control class. Then, based on the calculation of homogeneity test the data variant was homogeneous. It was found that F-obt > F- table (157 > 2.08). Meanwhile based on the result of the statistics calculation using independent t-test found that t-out = 7.69, it was higher than t-table = 2.02. it meant that there was any significant difference between the students who are taught using humanizing the classroom method and those who are taught using conventional method.